Leadership studies in brazilian events: the walked paths Estudos sobre liderança em eventos brasileiros: os caminhos percorridos - Silva, Luiz Henrique da; Ghedine, Tatiana; Pereira, Christiane Mendes Drozdek; Tutida, Alessandra Yula (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2021)
This research aimed to analyze the scientific research on leadership articles published in the EnANPAD and SemeAD annals in the period of 2014 - 2018. It is a bibliometric, quantitative and descriptive study.Publications from academic Personnel Management divisions were used, totaling 61 articles.The following were verified: number of articles, theme`s focus, most referenced articles, production characterization, concepts, methodologies and proposals for future research. The results demonstrate studies that sought to understand leadership as a process of influencing people, aiming to achieve common goals, understand and improve the leaders` role in the development of teams and improvement of organizational results.